PTD4-apoptin induces Bcl-2-insensitive apoptosis in human cervical carcinoma in vitro and in vivo. Issue 10 (November 2016) - Liu, Xiao-Wen; Yuan, Ping; Tian, Jun; Li, Ling-Jun; Wang, Yu; Huang, Song-Chun; Liu, Lin; Backendorf, Claude; Noteborn, Mathieu H.M.; Sun, Jun
Abstract : Worldwide, cervix carcinoma is among the most dangerous cancer types, and novel therapies are under development. Cancer treatments are often hampered because of lack of specificity. The chicken anemia virus-derived apoptin induces apoptosis selectively in tumor cells and leaves normal cells unharmed. Here, we have carried out in-vitro and in-vivo studies on the cytotoxic effect of apoptin in a cervix carcinoma model. Apoptin was fused to the protein transduction domain 4 (PTD4), enabling delivery of the fusion protein across cellular membranes. PTD4-apoptin protein is located in the nuclei of human cervical carcinoma HeLa cells and in the cytoplasm of normal cells L02. By MTT and flow cytometry analysis, we have proven that PTD4-apoptin protein induced apoptosis in the cervical carcinoma cells. PTD4-apoptin enhanced the level of active executioner caspase-3. Neither caspase-3 activation nor apoptin-induced accumulation of the mitochondrial outer-membrane protein Mfn-2 was affected by ectopic Bcl-2 expression. In contrast, apoptin-mediated AKT activation was inhibited by Bcl-2. In vivo, cervix carcinoma xenografts were treated for 7 days with PTD4-apoptin protein. The PTD4-apoptin treatment induced a decrease in the cervix carcinoma, whereas the PTD4-GFP protein-treated controls expanded significantly. TUNEL analysis showed that PTD4-apoptin protein induced apoptosis in cervix carcinoma cells, in contrast to the control PTD-GFP-treated ones. Our results indicate that apoptin is a potential anticancer agent for treating cervix carcinoma.